Tetramethylpyrazine alleviates cerebral ischemia-reperfusion injury via NRF2/HO-1/GPX4-mediated ferroptosis inhibition - Hengpei Gong; Yinjun Lu; Lingfeng Wang; Xueyuan Gong; Jingfang Zhao; Zhenxin Li (Tissue and Cell, 2027)

Effect of sodium hexametaphosphate on the flotation separation of biotite and K-feldspar in the NaOL/DDA system - Xingyu Hu; Bo Mei; Lingfeng Shen; Wei Sun; Yanxiu Wang; Jinghua Huang; Li Wang (Minerals Engineering, 2026)

Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Selective flotation of lepidolite from albite and quartz using a Hyperbranched surfactant THQ-8: Insights through foam property and adsorption behavior - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Largemouth bass virus infection subverts immune-redox homeostasis in zebrafish and is associated with coordinated suppression of NF-κB and Nrf2 signaling - Lingfeng Guan; Xinyue Zhang; Ting Yu; Yang Liu; Jiamei Long; Runchang Zhou; Hua Huang; Jinglin Tan; Zhifeng Chen; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2026)

Wearable triboelectric sensor based on a single-line-contact electrode architecture for gesture recognition and human–machine interaction - Long Li; Jingyun Dai; Jiayang Lyu; Yifan Shen; Yanmin Guo; Lingfeng Du; Zhiqian Wei; Xiongtu Zhou; Yongai Zhang; Hyung-Soon Kim; Dianlun Li; Kun Wang; et al. (Chemical Engineering Journal, 2026)

Flotation of quartz from albite using oligomeric surfactant THQ-8 in synergy with NaOL - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Global ammonia (NH3) retrieval from the FY-3F satellite hyperspectral infrared atmospheric sounder and performance assessment - Zhili Deng; Yapeng Wang; Minqiang Zhou; Ling Gao; Lin Chen; Xifeng Cao; Lingfeng Zhang; Yuhan Jiang; Haiyang Dou; Xingying Zhang (Atmospheric Environment, 2026)

Substantial mitigation of nitrous oxide realized in a light-mediated and aeration-free microalgal-bacterial consortium system - Lingfeng Wang; Weican Shi; Yanlin Liu; Zhaoming He; Jianhua Guo; Shijian Ge; Shuang Qiu (Algal Research, 2026)

Integrating machine learning and deep learning with multiple molecular fingerprints for topoisomerase I inhibitor screening and lead identification - Huang Zeng; Xuerou Zheng; Jiayao Liu; Shengyuan Zhang; Hua Nie; Nan Wang; Lingfeng Wu; Chunfang Liu; Ming Zhai; Hao Yang; Jiunlong Yang; Bo Qiu (Molecular Diversity, 2026)

Multi-objective optimization of ship resistance and seakeeping using an improved Voronoi-based parallel sequential sampling method - Dongqin Li; Yu Zhang; Yanqing Yin; Wenwen Chen; Bohan Wang; Zishuai Wang; Lingfeng Lu (Ocean Engineering, 2026)

Reverse flotation desilication of bauxite Ore: unraveling the mechanism of Cu(II)-SDSo in selective separation of kaolinite from diaspore - Boai Zhang; Lingfeng Shen; Honghu Tang; Jianjun Wang; Wei Sun; Jianyong He; Li Wang (Minerals Engineering, 2026)

Intensive mariculture promotes molecular reorganization of dissolved organic matter in coastal waters - Kai Shen; Niangming Duan; Zhibing Jiang; Jiang Shen; Haibo Jiang; Hailong Huang; Lingfeng Zhou; Dongping Shi; Mei Li; Ying Kang; Yuanhao Wang; Xubiao Yu (Environmental Research, 2026)

Precursor-engineered lignin-derived Co/N-doped carbon for high-efficiency electrocatalytic HMF oxidation: The critical role of pretreatment history - Chenxin Jin; Yajun Liu; Lingfeng Li; Yihan Wang; Changzhou Chen; Jianchun Jiang (Biomass and Bioenergy, 2026)

Precipitation and shortwave radiation dominate vegetation recovery times from flash droughts across Köppen–Geiger climate zones - Lei Zou; Wenzhe Zhu; Jun Xia; Feiyu Wang; Dunxian She; Chengjian Liu; Jiayuan Xu; Lingfeng Zuo (Agricultural and Forest Meteorology, 2026)

Granular hydrogel gradient microenvironments drive functional osteochondral interface regeneration - Jing Wang; Wenbo Zhong; Chengxiang Sha; Yu Shen; Zhaowei Yin; Lingfeng Yuan; Bin Liang; Xi Zeng; Jing Zhang; Ziyi Yu (Chemical Engineering Journal, 2026)

Dynamic characterization of representative naval steels under high-velocity fragment impact and functional vulnerability assessment of naval propulsion-system components - WenCai Sun; HouXiang Wang; LingFeng Hu; YuAng Shi; JianNan Li; ZiChun Yang (Ocean Engineering, 2026)

Nanoplastic exposure induces exoskeletal misdevelopment in juvenile Tachypleus tridentatus: Compensatory hardening versus molecular suppression - Lingfeng Jiang; Youji Wang; James Kar-Hei Fang; Khor Waiho; Wei Liu; Jae-Seong Lee; Xiaowan Ma; Menghong Hu (Marine Pollution Bulletin, 2026)

Influence of substrate on emplacement of a large rock avalanche in the west-central Tibetan Plateau, China: Insights from geomorphology and sedimentology - AnWen Shi; Yongbo Tie; YuFeng Wang; QianGong Cheng; HaoRan Tian; Lingfeng Gong; XiaoHui Xiong (Geomorphology, 2026)

Partially etched Ti2AlN/Ti2N/TiN ternary composite as a synergistic catalyst for enhanced hydrogen storage kinetics and cycling stability of NaAlH4 - Chen Jin; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Clinical efficacy and mechanistic study of intrauterine administration of E bing angong Ye for the treatment of endometritis in sows - Yi-Meng Fan; Xinyi Zhou; Lu Wang; Xiyu Wen; Xueyan Wang; Lingfeng Peng; Luyao Wang; Zhihui Hao (Theriogenology, 2026)

A real-time hybrid testing strategy for offshore wind turbines under wind–wave–earthquake loads using a frequency-decoupled wind load simulator - Yingpeng Tian; Ying Xu; Junfan Zuo; Lingfeng Xiao; Tao Wang (Ocean Engineering, 2026)

Nickel incorporation engineering for synergistic regulation of oxygen vacancies and electronic band configuration in Bi2O3 nanosheets for high-performance supercapacitor electrodes - Lingfeng Li; Weihao Zhang; Xuexuan Luo; Xueyi Chang; Muqing Chen; Zhiyu Cheng; Yongfu Qiu; Yu Wang (Chemical Engineering Journal, 2026)

Potential predictability of global seasonal precipitation anomalies determined by climate modes - Yu Wang; Xiu-Qun Yang; Dejian Yang; Lingfeng Tao; Jiabei Fang; Xuguang Sun (Climate Dynamics, 2026)

Long-Term in situ Monitoring of Anchoring System and Preliminary Analysis of Monitoring Data - Luobin Zheng; Huiming Tang; Liangqing Wang; Changdong Li; Chengren Xiong; Zongxing Zou; Chenlu Wang; Lingfeng Zhu; Yifan Zhang (Journal of Earth Science, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

Multifunctional polyvinyl alcohol composites via melt blending with a bio-based P-N synergistic flame retardant: Achieving simultaneous enhancement in fire safety, UV shielding, and mechanical properties - Junsheng Guo; Wenzong Xu; Tao Yan; Jiayan Zhang; Xiaoyu Guo; Lingfeng Wang; Julan Liu (Chemical Engineering Journal, 2026)

Synergistic CeH2.51/graphene nanointerface engineering for enhanced kinetics and cycling stability of Mg(NH2)2–2LiH - Chen Jin; Haoyuan Zheng; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Polystyrene microplastics impede growth and induce behavioural toxicity in endangered juvenile horseshoe crabs (Tachypleus tridentatus) - Yi Jiang; Zhiyuan Yang; Lingfeng Jiang; Cheong-Meng Chong; Shanza Gul; Youji Wang; Khor Waiho; Xiaowan Ma; Zhi Chen; Menghong Hu (Marine Environmental Research, 2026)

Environmental changes in the Okinawa Trough over the last 88 ka BP: Evidence from high-resolution bulk mineralogy - Lingfeng Luo; Xuguang Feng; Jianjun Zou; Xisheng Fang; Xinru Xue; Ruxi Dou; Baohua Han; Qingchao Wang; Aimei Zhu; Zhi Dong; Gang Yang; Xuefa Shi (Marine Geology, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

Comparative Analysis Provides Insights into the Phylogeny of Chamidae (Bivalvia: Veneroida) Through a Mitogenomic Approach - Jing Li; Yu Wang; Tao Xu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2026)

Enhancement mechanism of metal ions on lepidolite flotation in mixed NaOL/DDA system - Rui Xu; Lingfeng Shen; Jinghua Huang; Honghu Tang; Haisheng Han; Wei Sun; Li Wang (Minerals Engineering, 2025)

Plasmid engineering reveals size-dependent effects of plastic particles on horizontal gene transfer via transformation in Escherichia coli: Critical roles of plasmid size and plastic particle-bacteria spatial configuration - Lingfeng Zhu; Xuelan Chen; Zhihao Zhao; Mingzhu Huang; Yuechen Zhu; Hongtao Li; Yanna Shao; Mengrong Wang; Sicheng Xiong; Baoshan Xing (Journal of Hazardous Materials, 2025)

A refined incremental homogenization approach for heterogeneous nonlinear geomaterials without isotropization - Yongdong Li; Yuanming Lai; Zhaomin Lv; Xinwen Wang; Yian Zhou; Zipeng Qin; Lingfeng Guo; Lunyang Zhao (Computers and Geotechnics, 2025)

Ultra-stable and pH-universal photoelectrochemical photodetector achieved by CdSeTe/ZnS core-shell quantum dots - Jian Zhang; Yule Zhang; Songrui We; Han Zhang; Lingfeng Gao; Hao Wang; Chunxian Guo (Chemical Engineering Journal, 2025)

Sulfur vacancy-rich ZnIn2S4 via solvent engineering: Unveiling structure-defect-activity relationships for photocatalytic ranitidine degradation - Yilan Wang; Lingfeng Ouyang; Shuai Zhang; Zhanghong Zhou; Carolina Belver; Season Si Chen; Hao Wu (Chemical Engineering Journal, 2025)

A data-driven multi-objective optimisation framework for energy efficiency and thermal comfort in flexible building spaces - Huanbo Lyu; Daniel Herring; Hongkuan Chen; Shiqiao Zhou; Jianyu Zhang; Lingfeng Wang; Zheming Zuo; James Andrews; Michal kočvara; Fabian Spill; Jelena Ninic; Shuo Wang (Energy and Buildings, 2025)

Nanomaterial-powered immunotherapy: A next-generation therapeutic paradigm for bacterial infections - Xiaotong Sun; Shengnan Huang; Tong Ye; Lingfeng Xu; Yongfang Wang; Anqi Liu; Chao Liu; Yu Han; Mengfei Pang; Xuan Wu; Xin Pang (Chemical Engineering Journal, 2025)

In situ electrocatalytic nitrate-to-nitrite conversion-driven anammox in MBRs for extremely efficient ammonium-containing wastewater treatment - Lingfeng Ni; Peifang Wang; Gang Zhou; Zibin Li; Yayi Wang (Water Research, 2025)

Devonian–Triassic tectonic evolution of the Western Qinling Orogenic Belt of central China: Insights from detrital zircon U Pb chronology and rock geochemistry - Yan Zhang; Shuang Dai; Futian Liu; Dongbao Guo; Lingfeng Qin; Zhongzhao Ding; Yongfa Chen; Xinnan Fang; Xiaojun Ma; Yu Wang; Hua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Transcriptomic insights into an ancient and endangered species: Adverse effects of nanopolystyrene on the behavior and energy metabolism of Tachypleus tridentatus - Lingfeng Jiang; James Kar-Hei Fang; Youji Wang; Xiaowan Ma; Jae-Seong Lee; Menghong Hu (Journal of Hazardous Materials, 2025)

Discharge and deposition metallogenic model of “Datangpo-type” manganese deposits in China: Geophysical evidence from deep electrical structure of manganese-bearing grabens - Bingnan Yang; Xiangyun Hu; Lingfeng Gao; Xiaoqing Shen; Weiyang Liao; Jiajun Wang; Liangjun Yuan (Journal of Asian Earth Sciences, 2025)

The Ran GTPase inhibits SGIV and RGNNV infection by upregulating host immune response in grouper - Xiaozhi Wen; Lingfeng Guan; Liqun Wang; Zihan Zhang; Xinyan Wei; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2025)

Nano-magnetoelectric biomimetic system promotes neural differentiation and reverses dopaminergic neuron damage for Parkinson's disease therapy - Jie Zhang; Jiahui Shi; Qiubo Yang; Haogang Guo; Lingfeng Guo; Guoliang Zhou; Yinyi Liu; Xiaolei Wang; Xian Hao; Yifei Yang (Chemical Engineering Journal, 2025)

Ultrasensitive SERS detection of cytokines through specific binding and multiple reporter molecules - Hairong Chen; Hengchang Zhang; Lingfeng Duan; Kaidi Sun; Rui Li; Yunxia Wang; Jiacheng Yao; Changchun Yan; Ying Liu; Ying Wu; Guohai Yang; Caiqin Han (Analytica Chimica Acta, 2025)

A novel dual-branch spatial-spectral attention fusion model and method: A case study for the detection of nicotine content in tobacco leaves - Fukang Xing; Rongguang Zhu; Shichang Wang; Lingfeng Meng; Fujia Dong; Songfeng Wang; Jie Ren; Zongxiu Bai; Yapeng Kang (Computers and Electronics in Agriculture, 2025)

Positive contributions of China's protected areas in biodiversity conservation and carbon storage under future climate change - Xuede Dong; Jirui Gong; Frank Yonghong Li; Lingfeng Mao; Weiyuan Zhang; Siqi Zhang; Guisen Yang; Chenyi Yan; Ruijing Wang; Shangpeng Zhang; Tong Wang (Science of The Total Environment, 2025)

Biosynthesis of ag nanoparticles by aqueous extracts from soybean pods and tea residues: enhanced antioxidant and antibacterial activity - Chun Song; Lingfeng Wang; Hanghang Yu; Yu Wang (Nanotechnology for Environmental Engineering, 2025)

Theoretical Model for Load Distribution in Active–Passive Support Systems of Large-Section Tunnels - Zhongxin Xin; Jie Dong; Bo Wang; Lingfeng Sun (Geotechnical and Geological Engineering, 2025)

Sliding-window enhanced olfactory visual images combined with deep learning to predict TVB-N content in chilled mutton - Shichang Wang; Yixin Zhang; Rongguang Zhu; Fukang Xing; Jiufu Yan; Lingfeng Meng; Xuedong Yao (Meat Science, 2025)

Cascade assembly of metal-organic Framework–Immobilized enzyme complexes for enhanced catalytic activity and sensing applications - Zuyao Fu; Hao Wang; Lingfeng Yang; Zhaoyang Ding; Jing Xie (Chemical Engineering Journal, 2025)

Glyceryl lignin enhances lytic polysaccharide monooxygenase (LPMO) oxidative activity via electron transfer and H2O2 generation: Mechanistic insights from glycerol pretreatment - Lingfeng Long; Han Wang; Chong Wang; Shoushuai Feng; Hailin Yang; Xianzhi Meng; Chen Huang; Arthur J. Ragauskas (Chemical Engineering Journal, 2025)

High-throughput screening and inhibition mechanism analysis of Bacillus licheniformis BL-4 as an antagonistic strain for Lactobacillus panis - Lingfeng Yi; Xinyue Li; Menglin She; Yaokang Wu; Jianghua Li; Guocheng Du; Long Liu; Li Wang; Yanfeng Liu (Systems Microbiology and Biomanufacturing, 2025)

Characteristics of phosphorus distribution and mechanisms of phosphorus release through migration and transformation in the sediments of deep-water reservoirs in mountainous areas - Lingfeng Wang; Feng Zhong; Haibo Li; Zhenbo Sun; Wenjie He (Journal of Environmental Chemical Engineering, 2025)

Safety and Probiotics Evaluation of Bifidobacterial Genomes Isolated from Probiotic Products - Jue Li; Yinhuan Wang; Xingyu Xu; Xiaoling Zheng; Zhengnan Wang; Xiaofeng Chen; Lei Wang; Lingfeng Mao; Wangqin Ge; Huijun Liu; Wenwen Gao; Tingzhang Wang; et al. (Current Microbiology, 2025)

Near-complete assembly and comprehensive annotation of the wheat Chinese Spring genome - Zijian Wang; Lingfeng Miao; Kaiwen Tan; Weilong Guo; Beibei Xin; Rudi Appels; Jizeng Jia; Jinsheng Lai; Fei Lu; Zhongfu Ni; Xiangdong Fu; Qixin Sun; et al. (Molecular Plant, 2025)

Microplastics magnify inhibitive effects of perfluorooctanoic acid on the marine microbial loop - Peichun Lin; Xiaokun Liu; Zuyuan Gao; Yelinzi Yuan; Hongbin Liu; Lingfeng Huang; Zhili He; Qinglu Zeng; Shanquan Wang (Environmental Research, 2025)

Adaptive Responses in Byssal Growth and Shedding: Insights from Pteria penguin Under Thread Trimming and Non-Trimming Conditions - Hebert Ely Vasquez; Shangkun Wei; Guoliang Yang; Lingfeng Wang; Peixuan Yu; Mingyue Dong; Chao Yuan; Xing Zheng (Journal of Marine Science and Engineering, 2025)
Bivalves use byssal threads for attachment and locomotion, periodically shedding and regenerating them. In the winged pearl oyster Pteria penguin—known for its strong byssus and its role in the pearl industry—shedding may occur when the byssal stalk reaches a critical size, although the underlying mechanism remains unclear. This study investigated whether artificial manipulation of the byssus (via trimming) could stimulate thread production and promote shedding in adult P. penguin from two size groups. Byssal threads attached to the substrate were trimmed every 3–5 days over a 30-day period and compared to untrimmed controls. Oysters with trimmed byssus produced significantly more threads, with smaller individuals outperforming larger ones in both thread count and byssal stalk diameter. Moreover, small oysters exhibited a higher frequency of complete byssal shedding. These findings suggest that trimming stimulates thread production and accelerates stalk thickening, potentially triggering shedding due to spatial constraints at the attachment site. This response appears to reflect an adaptive mechanism for maintaining effective attachment and may help explain how mechanical or environmental cues influence byssal dynamics. Understanding this process offers new insight into the behavioral and physiological plasticity of P. penguin, with potential applications in pearl oyster management and aquaculture.

Co-infection by RGNNV and V. rotiferianus in golden pompano: Insights into disease risks and immune responses - Xinshuai Li; Lingfeng Guan; Cuiyu Liu; Jinpeng Chen; Xin He; Yanwei Li; Shaowen Wang; Qiwei Qin; Min Yang (Aquaculture, 2025)

A 1D spectral approach for efficient modal identification of thin-walled members in shell finite element models - Yiling Dai; Shaokuai Wang; Mingming Xiang; Lingfeng Yin; Zhanjie Li (Engineering Structures, 2025)

Preparation of SCOF/UiO-66-NH2 immobilized laccase biocatalytic membrane for micropollutants removal from water - Tiantian Wang; Lingfeng Zhao; Guanhua Liu; Xiaoyang Yue; Xiaobing Zheng; Li Ma; Yunting Liu; Mimi Chen; Yanjun Jiang (Chemical Engineering Journal, 2025)

Exploring the relationship between walls and urban biodiversity: a systematic review - Qinghua Xu; Ranxu Jia; Ranyang Zhang; Yuncai Wang; Lingfeng Mao; Hui Wang (Urban Ecosystems, 2025)

Advanced design of the crushing chamber for the sugarcane top silage cutter in harvester with experiments and simulation - Peng Huo; Shaochun Ma; Jun Qian; Weiqing Li; Baocheng Zhou; Wei Liu; Wenpeng Liang; Wenzhi Li; Changyu Wang; Sha Yang; Lingfeng Li; Yechen Li; et al. (Computers and Electronics in Agriculture, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The coupling of ultra-nano oxygenation and in-situ sediment remediation technology jointly promotes phosphorus enrichment and nitrogen removal - Lu Cao; Lingling Wan; Chunhui Xi; Zijun Zhou; Siyang Wang; Lingfeng Cao; Zhicheng Min; Xiankun Chen; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Journal of Water Process Engineering, 2025)

Co-infection of nervous necrosis virus and Vibrio harveyi increased mortality and worsened the disease severity in the orange-spotted grouper (Epinephelus coioides) - Lingfeng Guan; Xinshuai Li; Jinpeng Chen; Liqun Wang; Xinyue Zhang; Hongyan Sun; Yanwei Li; Min Yang; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2025)

ABTrans: A Transformer-based Model for Predicting Interaction between Anti-Aβ Antibodies and Peptides - Yuhong Su; Xincheng Zeng; Lingfeng Zhang; Yanlin Bian; Yangjing Wang; Buyong Ma (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Oral pH-Sensitive Solid Self-Microemulsion of Norcantharidin Wrapped in Colon-Coated Capsule for Selective Therapy of Colorectal Carcinoma - Xia Liu; Wenyou Fang; Wenjie Lu; Mingchao Xu; Zijun Wu; Dan Su; Lingzhen Ding; Qing Zhang; Jinguang Ouyang; Tianming Wang; Lingfeng Sun; Song Gao; et al. (AAPS PharmSciTech, 2025)

Survival and physiological responses of pearl oyster Pinctada maxima seedlings: Comparative analysis of wet (submerged) and dry (waterless) transportation methods - Xing Zheng; Ze Yin; Lingfeng Wang; Shangkun Wei; Meng Zhang; Xinfei Shao; Hebert Ely Vasquez; Zhifeng Gu (Aquaculture, 2025)

Response of nitrifiers to gradually increasing pH conditions in a membrane nitrification bioreactor: Microbial dynamics and alkali-resistant mechanism - Weican Shi; Zhaoming He; Jiahui Lu; Lingfeng Wang; Jianhua Guo; Shuang Qiu; Shijian Ge (Water Research, 2025)

Martian Chaos terrain fracture geometry indicates drainage and compaction of laterally heterogeneous confined aquifers - Joseph S. Levy; Thomas F. Subak; Ian Armstrong; Izzy King; Lingfeng Kuang; Lily Kuentz; James H. Gearon; Sophie Naylor; M.C. Rapoza; Haobo Wang (Icarus, 2025)

Impact performance of curved double arrow and stacked Miura-ori panels - Zhejian Li; Lingfeng Wang; Ruofei Yan; Yuanpeng He; Hong Hao; Yuanzheng Lin; Wensu Chen (Engineering Structures, 2025)

Tracing offshore marine ecosystem asset changes based on physical accounting: A case of Xiamen Sea Area - Junbo Wang; Benrong Peng; Lingfeng Huang; Keliang Chen (Ocean & Coastal Management, 2024)

Abrupt enhanced Pacific warm water intrusion into the Sea of Okhotsk since the early Holocene - Xuguang Feng; Jianjun Zou; Xuefa Shi; Zhengquan Yao; Zhi Dong; Jiang Dong; Yonghua Wu; Ruxi Dou; Hualong Jin; Aimei Zhu; Xiaojing Wang; Qingchao Wang; et al. (Quaternary Science Reviews, 2024)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Development and application of a low-cost and portable multi-channel spectral detection system for mutton adulteration - Shichang Wang; Binbin Fan; Zhongtao Huang; Zongxiu Bai; Rongguang Zhu; Lingfeng Meng (Biosystems Engineering, 2024)

Mapping critical soil moisture thresholds of water stress for global grasslands - Lingfeng Shi; Yanlian Zhou; Wei He; Zhoutong Dong; Zhuoyou Jiang; Yuyan Wang; Yibo Liu; Weimin Ju; Zheng Duan (Journal of Hydrology, 2024)

Double network hydrogel confined MXene/Liquid metal by dynamic hydrogen bond for high-performance wearable sensors - Yuanwan Lou; Jingkun Wang; Yubo Peng; Xiaona Wang; Jianan Zhang; Lingfeng Chen; Wenchao Gao; Zhipeng Gao; Xiaona Li; Weiyi Chen; Min Zhao (Chemical Engineering Journal, 2024)

Diversification in birds is promoted by plant diversity, topographic heterogeneity and stable paleoclimate - Xinyu Wang; Lu Miao; Xiongwei Huang; Lingfeng Mao; Tianlong Cai; Jens‐Christian Svenning; Gang Feng (Journal of Biogeography, 2024)
Aims Long‐term climate stability, contemporary climate and environmental heterogeneity have been linked to bird diversity patterns through their direct impacts on diversification rate, as well as through their indirect effects on plant species richness, which could also directly and indirectly affect bird diversity. This study aimed to quantitatively assess whether these potential drivers could indirectly affect bird species richness through their direct effects on the diversification rate in birds in eastern Asia. Location Mainland China. Taxon Birds. Methods Using the distribution data of 1127 bird species across 320 prefecture cities in China and a phylogenetic tree of these bird species, we analysed the distribution patterns of bird species richness and diversification rate of all birds, passerine birds and non‐passerine birds, respectively. We also investigated their relationships with long‐term climate stability, contemporary climate, elevation range and plant diversity using ordinary least squares regression model and simultaneous autoregressive model. In addition, structural equation model was used to analyse whether these drivers could indirectly affect bird species richness through their direct effects on bird diversification rate. Results The results showed that bird species richness and diversification rate were highest in southwestern China. Additionally, diversification rate for passerine birds was higher than non‐passerine birds and all birds. Regression analyses revealed that plant species richness was the variable most associated with bird species richness and diversification rate across the three groups. Notably, results from structural equation model indicated that plant species richness, elevation range and glacial–interglacial climate change can indirectly influence bird species richness by directly affecting diversification rates. Main Conclusions These findings emphasize the importance of considering diversification rate when understanding the geographic distribution patterns of bird diversity. The direct and indirect effects of plant species richness, elevation range and glacial–interglacial climate change on bird diversity highlight the crucial role of mountain regions with higher plant diversity and stable paleoclimate in forming and maintaining biodiversity.

Urbanization significantly increases greenhouse gas emissions from a subtropical headwater stream in Southeast China - Mutan Dai; Yuanhui Xu; Yegenberdy Genjebay; Lingfeng Lu; Chuan Wang; Hao Yang; Changchun Huang; Tao Huang (Science of The Total Environment, 2024)

High pre-tension reinforcing technology and design for ultra-shallow buried large-span urban tunnels - Qi Wang; Huayong Wei; Bei Jiang; Xuepeng Wang; Lingfeng Sun; Manchao He (International Journal of Rock Mechanics and Mining Sciences, 2024)

Unveiling the structure-performance of MoO3/La2O2CO3 for ultra-deep aerobic oxidative desulfurization of diesel - Shijia Shao; Hui Liu; Xiangdong Wang; Lingfeng Jia; Shuhui Zhou; Yan Huang; Huifang Cheng; Feng Liu; Yun Wang; Jixing Liu; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Influence of corrosion on seismic performance of steel beam-to-column connections - Yuelin Zhang; Cheng Fang; Wei Wang; Lingfeng Wu; Peng Cao (Engineering Structures, 2024)

FSP1-mediated ferroptosis in cancer: from mechanisms to therapeutic applications - Ran Gao; Jinge Wang; Jingjing Huang; Tong Wang; Lingfeng Guo; Wenlu Liu; Jialu Guan; Desen Liang; Qinghui Meng; Huayang Pan (Apoptosis, 2024)

Research and application of a tunnel active–passive cooperative control mechanism - Qi Wang; Lingfeng Sun; Bei Jiang; Zhongxin Xin; Yueru Guo (Tunnelling and Underground Space Technology, 2024)

Doped microspheres for whispering gallery mode microlasing - Xiaoxuan Wang; Chaoyang Huang; Chuansheng Xia; Feifei Qin; Gangyi Zhu; Lingfeng Mao; Yi Ma; Zengliang Shi; Qiannan Cui; Chunxiang Xu (Science Bulletin, 2024)

Hypoxia impairs cellular energy allocation in the juvenile horseshoe crab Tachypleus tridentatus - Lingfeng Jiang; Meilian Huang; Chunhua Liu; Mohamed H. Abo-Raya; Xiaowan Ma; Youji Wang; Menghong Hu (Journal of Experimental Marine Biology and Ecology, 2024)

Strength and behavior of axially and eccentrically loaded built-up closed sections using four cold-formed steel open sections - Lingfeng Yin; Shaokuai Wang; Yongbiao Wang; Tianyang Deng; Zhanjie Li (Engineering Structures, 2024)

Cation-driven self-assembly of core–shell covalent organic frameworks@Ti3CN MXene nanospheres for high-performance aqueous zinc-ion hybrid supercapacitors - Kaige Zhang; Quan Zong; Kuixing Ding; Ying Wang; Lingfeng Gao; Dongdong Xu; Zhonghui Chen; Huanan Yu (Chemical Engineering Journal, 2024)

Wide-bandgap donor polymers from organic photovoltaics as dopant-free hole transport layers for perovskite solar cells - Hongtao Lai; Xin Yang; Liujiang Zhang; Leyu Bi; Binqiang Tian; Huanhuan Wang; Xingyu Gao; Lingfeng Lu; Bin Kan; Xiaofei Ji; Qiang Fu (Chemical Engineering Journal, 2024)

Physiological and transcriptomic analysis revealed that the accumulation of reactive oxygen species caused the low temperature sensitivity of Liriodendron × sinoamericanum - Ye Lu; Lingfeng Hu; Long Yu; Shuang Liang; Haoxian Qu; Mingqi Wang; Zhaodong Hao; Liming Yang; Jisen Shi; Jinhui Chen (Plant Science, 2024)

Impact of hypoxia on glucose metabolism and hypoxia signaling pathways in juvenile horseshoe crabs Tachypleus tridentatus - Lingfeng Jiang; Yueyong Shang; Yuntian Shi; Xiaowan Ma; Malik ShahZaib Khalid; Meilian Huang; James Kar-Hei Fang; Youji Wang; Kianann Tan; Menghong Hu (Marine Environmental Research, 2024)

Rain gardens enhance the taxonomic richness but not the abundance of soil invertebrates in urban ecosystems - Jingjing Wang; Lihao Guo; Saige Xu; Yan Zhu; Lingfeng Mao (Ecological Engineering, 2024)

Nanofiltration membrane with modified nano-gradient structure and positive charge for Li separation from high Mg/Li ratio brine - Peng Zhao; Fei Guo; Lingfeng Wang; Huange Zhen; Ning Zhang; Shaohua Yin; Guoli Zhou; Xuehua Ruan; Gaohong He; Xiaobin Jiang (Desalination, 2024)

Seipin Deficiency Leads to Energy Dyshomeostasis via Inducing Hypothalamic Neuroinflammation and Aberrant Expression of Neuropeptides - Wenli Cui; Hong Chen; Lingfeng Lei; Wenru Wang; Kah-Leong Lim; Chengwu Zhang; Li Lu (NeuroMolecular Medicine, 2024)

How does green manufacturing promote the recycling of renewable solid waste and carbon reduction? - Baozhuang Niu; Lingfeng Wang (Resources, Conservation and Recycling, 2024)

Parallel path following control of cyber-physical maritime autonomous surface ships based on deep neural predictor - Lingfeng Li; Anqing Wang; Bing Han; Dan Wang; Tieshan Li; Zhouhua Peng (Ocean Engineering, 2024)

Advancing C5+ hydrocarbons fuels production: An interpretable machine learning framework for Co-catalyzed syngas conversion - Zhilong Yuan; Ye Wang; Lingfeng Zhu; Congcong Zhang; Yifei Sun (Fuel, 2024)

Development of novel single fuel cell based on composite polar plates for highly efficient power generation - Caiying Zhou; Yancheng Wang; Deqing Mei; Wenze Mao; Lingfeng Xuan (Fuel, 2024)

Differentiation of fungal trophic guilds to long-term nitrogen addition in a poplar plantation - Nan Yang; Jiangbao Zhang; Jiani Hua; Baohan Song; Tianyi Wang; Wei Xing; Guobing Wang; Lingfeng Mao; Honghua Ruan (Forest Ecology and Management, 2024)

Impact of a gravity wave process on the upper stratospheric ozone valley on the Qinghai-Tibetan Plateau - Jundong Wang; Lingfeng Wan; Shujie Chang; Haotian He (Theoretical and Applied Climatology, 2024)
Atmospheric gravity waves are essential meso-small-scale oscillations that facilitate material exchange within the atmosphere. These waves can significantly affect the ozone layer in the Upper Troposphere and Lower Stratosphere (UTLS) on the Qinghai-Tibetan Plateau. However, the influence of gravity wave dynamic processes on upper stratospheric ozone has rarely been studied. This paper identifies the gravity waves on the Tibetan Plateau based on ECMWF Reanalysis 5 (ERA5) data, analyzes the response of the upper stratospheric ozone to the event, and simulates the dynamic propagation mechanism of gravity waves by the Weather Research and Forecasting (WRF) model. This analysis reveals that between 15:00 and 21:00 UTC on July 29, 2015, gravity waves propagated from the surface of Tibetan Plateau (450 hPa) up to the upper stratosphere (20 − 3 hPa) in an arc-shaped structure and tilted to the east with height. The gravity wave signals started to weaken at 21:00 UTC on the same day. Influenced by the easterly rapids, gravity waves partially broke near 3 hPa at 02:30 UTC on July 30, but gravity wave signals were still present, and gravity waves completely broke and released energy at 04:00 UTC. During this process, ozone in the 20–3 hPa region (upper stratosphere) on the Qinghai-Tibetan Plateau responds well to gravity waves, and the ozone mixing ratio began to drop in ozone concentration 30 min after the partial breakup (03:00 UTC). The ozone dropped drastically by about 0.014 ppmv from 04:00 to 05:00 UTC. The WRF simulation results agree well with ERA5 and accurately capture the intricate characteristics of gravity waves. Furthermore, the breakup of gravity waves caused a total drop in ozone of 0.024 ppmv.

Exposure, bioaccumulation, and risk assessment of organophosphate flame retardants in crayfish in the middle and lower reaches of the Yangtze River - Qiuhong Peng; Lingfeng Peng; Jin Liu; Yan Liu; Xin Liu; Jiaojiao Yin; Shuo Duan; Xiaofang Liu; Yuzhi Li; Zhiyong Gong; Qiao Wang (Science of The Total Environment, 2024)

Growth patterns and optimum habitat of Larimichthys crocea throughout ontogenesis based on a bioenergetics model - Bin Xie; Shin-ichi Ito; Lingfeng Huang; Haiqing Yu; Chenying Guo; Ziqin Wang (Regional Studies in Marine Science, 2024)

Vapor-liquid equilibrium measurement for carbon dioxide (CO2)+propylene (R1270) binary mixture at temperatures from subcritical to supercritical - Zirui Wu; Rui Sun; Lingfeng Shi; Peng Hu; Hua Tian; Xuan Wang; Gequn Shu (International Journal of Refrigeration, 2024)

Photothermal microneedle patch loaded with antimicrobial peptide/MnO2 hybrid nanoparticles for chronic wound healing - Guanyi Wang; Wang Wang; Zesheng Chen; Tao Hu; Lingfeng Tu; Xiaolong Wang; Weikang Hu; Sheng Li; Zijian Wang (Chemical Engineering Journal, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Saving the overlooked mangrove horseshoe crabs-A perspective from enhancing mangrove ecosystem conservation - Yuntian Shi; Shuhui Li; Yaowu Li; Lingfeng Jiang; Fahim Ullah Khan; Khor Waiho; Youji Wang; Menghong Hu (Marine Environmental Research, 2024)

A bioinspired setup to evaluate food graininess via tactile friction and vibration - Liwen Huang; Chengjin Du; Lingfeng Wang; Chaoyi Yuan; Jun Wang; Dongdong Du (Journal of Food Engineering, 2024)

An improved numerical manifold method for crack propagation of concrete gravity dams under seismic loads - Yujie Xu; Yuan Wang; Lingfeng Zhou; Qi Dong (Computers and Geotechnics, 2024)

A low-carbon CO2 ice rink technology for the Winter Olympics - Ligeng Li; Kai Liu; Hua Tian; Jinwen Cai; Christos N Markides; Jingyu Wang; Lingfeng Shi; Xuan Wang; Yitai Ma; Xingyu Liang; Gequn Shu (Science Bulletin, 2023)

Revealing the specificity of map method to predict the performance of a combined cooling and power cycle under operating conditions - Yu Yao; Lingfeng Shi; Jintao He; Xiaocun Sun; Bowen Lu; Yonghao Zhang; Hua Tian; Xuan Wang; Gequn Shu (Journal of Cleaner Production, 2023)

Grouper Rab1 inhibits nodovirus infection by affecting virus entry and host immune response - Lingfeng Guan; Xiaozhi Wen; Zihan Zhang; Liqun Wang; Xinyue Zhang; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2023)

Enhancing effect of cobalt phthalocyanine dispersion on electrocatalytic reduction of CO2 towards methanol - Tianxiang Guo; Xilai Wang; Xiaodong Xing; Zhixiang Fu; Changxin Ma; Alemayehu Hailu Bedane; Lingfeng Kong (Environmental Science and Pollution Research, 2023)

Experimental studies on active oxygen control performance of solid PbO mass exchanger in liquid lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Zhenhua Sheng; Xiaobo Li; Muran Qi; Yifeng Wang; Lingfeng Yang; Xu Tu; Hao Wu; Fang Liu; Zhangpeng Guo; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Storage allocation rules to meet shared water demands for optimal operation of reservoir water supply - Fang Wan; Yu Wang; Lingfeng Xiao; Qihui Chai (Irrigation and Drainage, 2023)
The priority principle of storage allocation rules of serial cascade reservoirs within an interbasin water supply can reduce water loss and reduce water supply times. Reasonable balancing curves for reservoirs in parallel are proposed, and the proportional distribution of water is determined to illustrate the optimal allocation rule for different reservoir scheduling periods. The mutation point and slope are used to describe the segmentation of reservoirs in parallel. Finally, the relative optimal water supply rule is obtained. Taking the reservoir groups in the lower reaches of the Luanhe River basin as the research object, the results show that the water supply obtained by the balancing curve is increased by approximately 4% compared with the compensation regulation, and wasted water is reduced by 10%. The results are close to the largest water supply, the annual average wasted water and the guarantee rate obtained by dynamic programming. The suggested method can achieve the operation goal effectively and improve the operation performance of the shared water demands for the reservoir water supply. This article highlights the superior results obtained compared with the current storage allocation rules to meet shared water demands.

Performance of potentiometric oxygen sensors with LSCF electrode in lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Lingfeng Yang; Muran Qi; Xiaobo Li; Yifeng Wang; Zhenhua Sheng; Xu Tu; Gaoxiang Xu; Boqing Li; Hao Wu; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Low-photovoltage-loss pringting perovskite solar cells in ambient air through ink synergistic engineering - Yifan Lv; Kaiyu Wang; Ai Lan; Lingfeng Chao; Changshun Chen; Jinpei Wang; Qing Yao; Jianxin Chen; Tengfei Pan; Yajing Li; Hui Zhang; Yingdong Xia; et al. (Chemical Engineering Journal, 2023)

Association of Urinary Strontium with Cardiovascular Disease Among the US Adults: A Cross-Sectional Analysis of the National Health and Nutrition Examination Survey - Sibo Wang; Jiateng Sun; Lingfeng Gu; Yaxin Wang; Chong Du; Hao Wang; Yao Ma; Liansheng Wang (Biological Trace Element Research, 2023)

Phylogenomic resolution of Imparidentia (Mollusca: Bivalvia) diversification through mitochondrial genomes - Yu Wang; Yi Yang; Lingfeng Kong; Takenori Sasaki; Qi Li (Marine Life Science & Technology, 2023)
Despite significant advances in the phylogenomics of bivalves over the past decade, the higher-level phylogeny of Imparidentia (a superorder of Heterodonta) remains elusive. Here, a total of five new mitochondrial sequences ( Chama asperella , Chama limbula , Chama dunkeri , Barnea manilensis and Ctena divergens ) was added to provide resolution in nodes that required additional study . Although the monophyly of Lucinida remains less clear, the results revealed the overall backbone of the Imparidentia tree and the monophyly of Imparidentia. Likewise, most relationships among the five major Imparidentia lineages—Lucinida, Cardiida, Adapedonta, Myida and Venerida—were addressed with a well-supported topology. Basal relationships of Imparidentia recovered Lucinidae as the sister group to all remaining imparidentian taxa. Thyasiridae is a sister group to other imparidentian bivalves (except Lucinidae species) which is split into Cardiida, Adapedonta and the divergent clade of Neoheterodontei. Neoheterodontei was comprised of Venerida and Myida, the former of which now also contains Chamidae as the sister group to all the remaining venerid taxa. Moreover, molecular divergence times were inferred by calibrating nine nodes in the Imparidentia tree of life by extinct taxa. The origin of these major clades ranged from Ordovician to Permian with the diversification through the Palaeozoic to Mesozoic. Overall, the results obtained in this study demonstrate a better-resolved Imparidentia phylogeny based on mitochondrial genomes.

Effect of extreme pH conditions on methanogenesis: Methanogen metabolism and community structure - Shuang Qiu; Xingchen Zhang; Wenhao Xia; Zimu Li; Lingfeng Wang; Zhipeng Chen; Shijian Ge (Science of The Total Environment, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Mediation Effect of Body Mass Index on the Association of Urinary Nickel Exposure with Serum Lipid Profiles - Sibo Wang; Tiankai Shan; Jun Zhu; Qiqi Jiang; Lingfeng Gu; Jiateng Sun; Yulin Bao; Bo Deng; Hao Wang; Liansheng Wang (Biological Trace Element Research, 2023)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Surface display of major capsid protein on Bacillus subtilis spores against largemouth bass virus (LMBV) for oral administration - Quan Wang; Xia Liang; Yunshang Ning; Shijia Liu; Zengjian Liang; Zemiao Zhang; Yingjing Chen; Jinqiao Cao; Fubao Wang; Lingfeng Lan; Guangzhao Cheng; Youhua Huang; et al. (Fish & Shellfish Immunology, 2023)

Degradation of PAHs in soil by activated persulfate system with activated carbon supported iron-based bimetal - Congcong Zhang; Huifang Tian; Zhaoxu Wang; Lingfeng Zhu; Xingshuang Liu; Ye Wang; Yifei Sun (Science of The Total Environment, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

Chronic exposure to IQOS results in impaired pulmonary function and lung tissue damage in mice - Jianjun Gu; Daohui Gong; Yuxiu Wang; Tingting Feng; Jun Zhang; Suwei Hu; Lingfeng Min (Toxicology Letters, 2023)

The effects of natural weathering ages on mineralogical, physical, and chemical properties of stacking molybdenum tailings - Li Wang; Lingfeng Shen; Wei Sun; Bin Ji; Honghu Tang (Environmental Science and Pollution Research, 2022)

Combined toxicity of chlorpyrifos, abamectin, imidacloprid, and acetamiprid on earthworms (Eisenia fetida) - Miaomiao Teng; Xiaoli Zhao; Chen Wang; Lingfeng Zhou; Xiaowei Wu; Fengchang Wu (Environmental Science and Pollution Research, 2022)

Effect of Angiogenesis in Bone Tissue Engineering - Jianhao Huang; Qixiu Han; Meng Cai; Jie Zhu; Lan Li; Lingfeng Yu; Zhen Wang; Gentao Fan; Yan Zhu; Jingwei Lu; Guangxin Zhou (Annals of Biomedical Engineering, 2022)

A climate perspective of the quasi-stationary front in southwestern China: structure, variation and impact - Danping Cai; Lingfeng Tao; Xiu-Qun Yang; Xiaozhuo Sang; Jiabei Fang; Xuguang Sun; Weiping Wang; Hongming Yan (Climate Dynamics, 2022)
Yunnan–Guizhou quasi-stationary front (YGQSF) is a unique weather phenomenon that frequently occurs during the winter half year over the Yunnan–Guizhou Plateau in southwestern China. Most of the previous studies analyzed it only with synoptic cases. This study investigates the structure, variation, and impact of this front from a climate perspective, using long-term high-resolution atmospheric reanalyses and high-density station records for 1981–2016. An objective method quantifying YGQSF is proposed and three indexes are defined to measure its intensity, frequency, and location, respectively, with horizontal gradient of air potential temperature at a terrain-following level of sigma 0.995. With these indexes, climatological structure, subseasonal variability as well as climatic impact of the front are comprehensively examined. In climatology, YGQSF as a north–south-oriented low-level front is found to occur the most frequently during January–February–March, determined predominately by the coldness from the east of the front. The structure of the front identified essentially reflects an obstruction of high-terrain Yunnan (the western part of the plateau) to the low-level cold air mass, which makes near-surface cold northeasterly winds cease westward intruding and veer upward over relatively low-terrain Guizhou, transporting moisture upward and forming low clouds. A sharp climate contrast is thus formed between two sides of the front: cold, sunless, and continuously rainy Guizhou versus warm and sunny Yunnan. Furthermore, the front features significant subseasonal variations with periods at around 30 days and 60 days largely in its intensity. Anomalously strong YGQSF events which are caused 75% by the cold anomaly from the east but no more than 17% by the warm anomaly from the west yield different anomalous structures, but consistently amplify the sharp climate contrast between Yunnan and Guizhou.

Estimating the Impact of a Seasonal Fishing Moratorium on the East China Sea Ecosystem From 1997 to 2018 - Lingyan Xu; Puqing Song; Yuyu Wang; Bin Xie; Lingfeng Huang; Yuan Li; Xinqing Zheng; Longshan Lin (Frontiers in Marine Science, 2022)
Fisheries management policies (FMPs) have been implemented in coastal countries to ensure a sustainable supply of seafood and the recovery of species diversity. Because of the depletion of fishery stocks, China has introduced a series of FMPs since 1995, including a seasonal fishing moratorium (SFM), a zero-growth strategy, and a minimum mesh size for fishing nets. Here, we built two mass balance models for 1997–2000 (M1997) and 2018–2019 (M2018) using Ecopath with Ecosim 6.6 to illustrate the interannual changes over the past two decades in the East China Sea (ECS). We then simulated two dynamic scenarios from 1997 to 2018, SFM (M2018 SFM ) and no SFM (M2018 no-SFM ), to test the role of the SFM under fishing pressure in the ECS. Ecopath showed that the ECS ecosystem is becoming more mature, although it is still unstable, featuring lower total primary production/total respiration, longer cycles, faster organic material circulation speed, and a higher omnivorous degree. This suggests a slow recovery for the ECS ecosystem in the past two decades. The biomass of fish in the ECS—especially the planktivores, dominated by small-sized Benthosema pterotum —significantly increased in M2018 versus M1997, but there were fewer medium- and large-sized fish. The keystone species switched from the planktivores/piscivores dominated by Decapterus maruadsi in M1997 to planktivores in M2018. Ecosim illustrated that the SFM has positive effects on fishery resources recovery, especially for commercial fishes (i.e., large yellow croakers and hairtails), as reflected by the significantly higher predicted biomass of fish in M2018 SFM compared to M2018 no-SFM and M1997, although the bioaccumulation was consumed by the intense fishing pressure after the SFM. However, the M2018 SFM prediction for nektons was still lower than the actual value, especially for planktivores, which display a sharp increase in biomass. This should be partly attributable to the policy of the minimum mesh size (<5 cm was banned), which benefits B. pterotum due to its 3.5 cm maximum body size. Therefore, a series of FMPs, rather than only the SFM, functioned together in the ECS ecosystem. However, the mixed trophic impact indicated a negative impact if the fisheries were further developed. Fishery management in the ECS needs to be strengthened by extending the SFM and reducing fishing pressure after the SFM.

The relationship between green roofs and urban biodiversity: a systematic review - Linwen Wang; Hui Wang; Yuncai Wang; Yue Che; Zhiwei Ge; Lingfeng Mao (Biodiversity and Conservation, 2022)

Determination of trophic levels of marine fish in the Yellow Sea and northern East China Sea using nitrogen stable isotope (δ15N) analysis of otoliths - Huaiyu Bai; Yukun Wang; Tingting Zhang; Fangqun Dai; Lingfeng Huang; Yao Sun (Journal of Oceanology and Limnology, 2022)

Erratum to: Contribution of Water Vapor to the Record-Breaking Extreme Meiyu Rainfall along the Yangtze River Valley in 2020 - Licheng Wang; Xuguang Sun; Xiu-Qun Yang; Lingfeng Tao; Zhiqi Zhang (Journal of Meteorological Research, 2021)

Faster recovery of soil biodiversity in native species mixture than in Eucalyptus monoculture after 60 years afforestation in tropical degraded coastal terraces - Wenjia Wu; Luhui Kuang; Yue Li; Lingfeng He; Zhijian Mou; Faming Wang; Jing Zhang; Jun Wang; Zhi’an Li; Hans Lambers; Jordi Sardans; Josep Peñuelas; et al. (Global Change Biology, 2021)
Afforestation is an effective method to restore degraded land. Afforestation methods vary in their effects on ecosystem multifunctionality, but their effects on soil biodiversity have been largely overlooked. Here, we mapped the biodiversity and functioning of multiple soil organism groups resulting from diverse afforestation methods in tropical coastal terraces. Sixty years after afforestation from bare land (BL), plant species richness and the abundance of plant litter (398 ± 85 g m −2 ) and plant biomass (179 ± 3.7 t ha −1 ) in native tree species mixtures (MF) were restored to the level of native forests (NF; 287 ± 21 g m −2 and 243.0 ± 33 t ha −1 , respectively), while Eucalyptus monoculture (EP) only successfully restored the litter mass (388 ± 43 g m −2 ) to the level of NF. Soil fertility in EP and MF was increased but remained lower than in NF. For example, soil nitrogen and phosphorus concentrations in MF (1.2 ± 0.2 g kg −1 and 408 ± 49 mg kg −1 , respectively; p −1 and 523 ± 24 mg kg −1 , respectively; p

Contribution of Water Vapor to the Record-Breaking Extreme Meiyu Rainfall along the Yangtze River Valley in 2020 - Licheng Wang; Xuguang Sun; Xiuqun Yang; Lingfeng Tao; Zhiqi Zhang (Journal of Meteorological Research, 2021)

Phylogeny of Veneridae (Bivalvia) based on mitochondrial genomes - Yu Wang; Yi Yang; Hongyue Liu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Zoologica Scripta, 2021)
Veneridae is one of the most diverse families of bivalve molluscs. However, their phylogenetic relationships among subfamilies have been debated for years. To explore phylogenetic relationships of Veneridae, we sequenced 13 complete mitochondrial genome sequences from eight subfamilies and compared with available complete mitochondrial genome of other Veneridae taxa (18 previously reported sequences). Phylogenetic analyses using probabilistic methods recovered two highly supported clades. In addition, the protein‐coding gene order revealed a highly conserved pattern among the same subclade lineages. According to our molecular analyses, Tapetinae should be recognized as a valid subfamily, but the genera formed para‐polyphyletic clades. Chioninae was recovered not monophyletic that differs from a previously molecular phylogeny. Furthermore, the reconstructed chronogram calibrated with fossils recovered the Veneridae have originated during the early Permian (about 290 million years ago). Noticeably, programmed frameshift was found in the nad4 gene of Leukoma jedoensis , Anomalodiscus squamosus and Antigona lamellaris and cob gene of L. jedoensis . This is the first time that the presence of the programmed frameshift has been found in the protein‐coding genes of Heterodonta species. Our results improved the phylogenetic resolution within Veneridae, and a more taxonomic sampling analysis of the subfamily Chioninae is supposed to construct.

Insights into fouling behavior in a novel anammox self-forming dynamic membrane bioreactor by the fluorescence EEM-PARAFAC analysis - Yijing Zhu; Lijuan Cao; Lingfeng Ni; Yayi Wang (Environmental Science and Pollution Research, 2020)

High plant species richness and stable climate lead to richer but phylogenetically and functionally clustered avifaunas - Na Wang; Lingfeng Mao; Xueting Yang; Xingfeng Si; Yanping Wang; Wolf L. Eiserhardt; Gang Feng (Journal of Biogeography, 2020)
Aims Glacial–interglacial climate stability and contemporary climate could affect bird diversity through their direct effects on diversification and physiological tolerance, and indirect effects on plant species richness, which could provide more food and ecological niches. This study aims to quantitatively assess the direct and indirect effects of these drivers on species richness, phylogenetic and functional structure of bird assemblages. Location Mainland China. Taxon Birds. Methods Ordinary least squares models and simultaneous autoregressive models were used to test the associations between glacial–interglacial climate anomaly, contemporary climate, plant species richness, elevation range and species richness, phylogenetic structure, functional structure of bird assemblages in mainland China. Structural equation models were used to distinguish between direct and indirect effects of these variables on bird diversity. Results High bird species richness with phylogenetically and functionally clustered structure occurred in regions with more plant species and stable glacial–interglacial climate. Notably, the phylogenetically clustered bird assemblages were composed of young lineages. Contemporary precipitation and elevation range affected bird diversity through their indirect effects on plant species richness. Main Conclusions These findings suggest that more plant species and stable glacial–interglacial climate may promote bird diversity through their effects on in situ diversification and species dispersal rate in southwestern China. Therefore, the well‐preserved plant and bird diversity through the long‐term climate fluctuations should be of great importance of biodiversity conservation in China.

Impedimetric biosensor fabricated with affinity peptides for sensitive detection of Escherichia coli O157:H7 - Fan Shi; Lingfeng Gan; Yibing Wang; Ping Wang (Biotechnology Letters, 2020)

Three-Dimensional Fluid–Solid Coupling Numerical Simulation of Effects of Underlying Karst Cave on Shield Tunnel Through Sand Stratum - Wei Wang; Shiming Gao; Youwei Min; Lingfeng Liu; Jianping Chen (Geotechnical and Geological Engineering, 2019)

The impact of successive mass selection on population genetic structure in the Pacific oyster (Crassostrea gigas) revealed by microsatellite markers - Jingxiao Zhang; Qi Li; Qingzhi Wang; Rihao Cong; Jianlong Ge; Lingfeng Kong (Aquaculture International, 2018)

Genetic variation assessed with microsatellites in mass selection lines of the Pacific oyster (Crassostrea gigas) in China - Xubo Wang; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Amphipods fail to suppress the accumulation of Ulva lactuca biomass in eutrophic Yundang Lagoon - Xinqing Zheng; Lingfeng Huang; Qian Wang; Rongcheng Lin (Acta Oceanologica Sinica, 2014)

Response to selection for fast growth in the second generation of Pacific oyster (Crassostrea gigas) - Qingzhi Wang; Qi Li; Lingfeng Kong; Ruihai Yu (Journal of Ocean University of China, 2012)

Selection response and realized heritability for growth in three stocks of the Pacific oyster Crassostrea gigas - Qi Li; Qingzhi Wang; Shikai Liu; Lingfeng Kong (Fisheries Science, 2011)

Genetic variation and differentiation in wide ranging populations of razor clam (Sinonovacula constricta) inferred from AFLP markers - Jingbo Wang; Qi Li; Lingfeng Kong (Journal of Ocean University of China, 2010)

Genetic Structure of the Veined Rapa Whelk (Rapana venosa) Populations Along the Coast of China - Jianmin Yang; Qi Li; Lingfeng Kong; Xiaodong Zheng; Rucai Wang (Biochemical Genetics, 2008)

Genetic diversity and divergence among clam Cyclina sinensis populations assessed using amplified fragment length polymorphism - Yuming Zhao; Qi Li; Lingfeng Kong; Zhenmin Bao; Rucai Wang (Fisheries Science, 2007)

Seasonal variation of the glycogen enzyme activity in diploid and triploid Pacific oyster gonad during sexual maturation - Lingfeng Kong; Zhaoping Wang; Ruihai Yu; Qi Li; Rucai Wang (Journal of Ocean University of China, 2007)